An Archives for a University in Sub-Saharan Africa: The Case for the University of Science and Technology, Kumasi (Journal of Science and Technology, 2016)
Types of archival institutions are enumerated. The need for and usefulness of an archival collection for a university are stated Materials which should be kept in the archived institution preliminary decisions to be taken and facilities to be provided like storage facilities, policy, funding. staffing record centers and preservation methods are then stated. The strategy for setting up an archive for the University of Science and Technology, Kumasi is discussed Ways to be set for processing the materials and findings to be provided an further discussed. Basic rules to be obeyed for the conservation of archival materials as well as methods like lamination, reprography repair by paper and by leather among others are described Some major agents which militate against the successful preservation of archival documents are enumerated. The means through which they destroy documents are stated. Likely remedies are then performed to counteract the operations of these agents.